(untitled) (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: The aim of this investigation was to prepare multiple unit floating mini matrix tablets of pyridoxine hydrochloric (HCl) which is having an absorption window in the upper part of gastrointestinal tract, i.e., jejunum. Hence, this study was planned to formulate, characterize with in-vitro and in-vivo evaluation in human subjects. Materials and Methods: In this investigation, multiple unit floating mini matrix tablets of pyridoxine HCl were formulated using hydroxy propyl methyl cellulose K grade polymers along with ethyl cellulose by wet granulation method. The physicochemical characteristics of all the prepared batches were evaluated. The in-vitro buoyancy and in-vitro drug release studies were conducted in the study. Based on in-vitro buoyancy and in-vitro drug release, optimized formulation was selected and subjected to stability studies as per WHO and ICH guidelines for 6Â months. The optimized formulation was further subjected to X-ray studies to establish the in-vivo gastric residence time in human volunteers by replacing the drug with X-ray grade barium sulfate. Results: The physicochemical characteristics of all the prepared batches were found to be satisfactory. All the prepared batches showed good in-vitro buoyancy and it was observed that the mini tablets remained buoyant for more than 12 h. The formulation FP8, which released complete drug release in 12 h with minimum floating lag time of 16 Â± 2.54, was considered as optimized formulation. The stability studies indicated that the optimized formulation is stable during its stability period. The in-vivo radiographic studies revealed that the mini tablets remained in the stomach up to 6 h in human volunteers and altered its position without any adhesion to walls of stomach. Conclusion: Based on in-vitro characteristics and in-vivo radiographic studies, it can be concluded that the best formulation FP8 by choosing multiple unit floating matrix tablets could improve patient compliance and ensure better drug absorption.